Effects of placebos vs. SMS reminders on homework compliance in cognitive behavioral therapy for depression: a randomized trial - Nina Jurinec; Anne Schienle (Mediterranean Journal of Clinical Psychology, 2022)
Background: Nonadherence to homework assignments is a frequent problem among patients with depression during cognitive-behavioral therapy (CBT). The present study investigated the effects of two additional treatment components of CBT: a placebo and SMS (short message service) reminders. These components aimed at improving homework compliance (the practicing of a daily relaxation exercise at home) during a four-week outpatient program. Subjects and Methods: Eighty-six patients diagnosed with major depressive disorder were randomly assigned to one of three groups: ‘Coping with Depression’ course (treatment as usual; TAU group), ‘Coping with Depression’ course with additional daily placebo treatment (PLA group), or ‘Coping with Depression’ course with additional daily SMS reminders (SMS group). The placebo (sunflower oil) was introduced as a natural medicine to mobilize the body’s natural healing powers. SMS messages were sent out once a day to remind the patients of their homework. Results: The placebo group showed better homework compliance than the two other groups with improved quantity and quality of relaxation exercises. The SMS group practiced more often than TAU but did not differ in homework quality (relaxation level) from TAU. All groups showed a significant reduction of depression symptoms at the end of the course with the most pronounced reduction in the PLA group. Conclusions: The results suggest that placebo treatment is more effective than SMS reminders to support relaxation training in patients with depression. Additionally, the placebo was associated with a larger reduction of depression symptoms.